(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2015)
Here, we analyze the way the measurement of the speed of light is made and show that the relative time is not implied by the constancy of the speed of light in vacuum for all observers. It is rather the universal time that is consistent with the way the speed of light can be measured.